Robert B. Parker's Little white lies [compact disc, unabridged] - Parker, Robert B., 1932-2010; Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Spenser novel., 2017)
Boston PI Spenser and right hand Hawk follow a con man's trail of smoke and mirrors in the latest entry of the iconic crime series. After conning everyone from the cable news shows to the local cops, it looks like the grifter's latest double cross may be his last.